2008
DOI: 10.1017/s1138741600004315
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of University Students' Academic Achievement by Linear and Logistic Models

Abstract: University students' academic achievement measured by means of academic progress is modeled through linear and logistic regression, employing prior achievement and demographic factors as predictors. The main aim of the present paper is to compare results yielded by both statistical procedures, in order to identify the most suitable approach in terms of goodness of fit and predictive power. Grades awarded in basic scientific courses and demographic variables were entered into the models at the first step. Two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Different approaches have been applied to predicting student academic performance, including traditional mathematical models [3,4] and modern data mining techniques [5][6][7]. In these approaches, a set of mathematical formulas was used to describe the quantitative relationships between outputs and inputs (i.e., predictor variables).…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been applied to predicting student academic performance, including traditional mathematical models [3,4] and modern data mining techniques [5][6][7]. In these approaches, a set of mathematical formulas was used to describe the quantitative relationships between outputs and inputs (i.e., predictor variables).…”
Section: Introductionmentioning
confidence: 99%
“…Those four predictors are Sex (male and female), type of high school (Medicine and Engineering), Type of middle school institution (Public and Private), and Location (Montevideo and Inland). The result for this study found that the students with better grades in the first year of faculty have less risk of curricular lag in the future (Ayan and Garcia, 2008). On the contrary, Bydzovska and Popelinsky (2014) investigated how Educational Data Mining can help predict weak and good students.…”
Section: Educational Data Miningmentioning
confidence: 87%
“…Cramer's V score [70] 21 Data mining [11], [80] 9 Logistic regression [35], [38], [61], [63], [64], [77], [79], [81], [82] 22…”
Section: Analysis Techniques and Methodsmentioning
confidence: 99%